Local perceptions and postures towards the SPA “Ria de Aveiro” - Sumares, David
It has been widely argued that guaranteeing the participation of local stakeholders is a key factor for the successful implementation of the Natura 2000 Network. One of the most vital elements for guaranteeing local participation in this context may be the image that the network enjoys among local authorities and stakeholders. Perceptions towards Natura 2000 result from the way the network has been implemented so far, and may simultaneously play an important role in fostering acceptance regarding the necessary compromises of further stages of implementation, i.e., the adoption of management and conservation measures. This article presents a critical survey on the positions of key politicians and employees of municipalities that share an important part of the Ria de Aveiro, an important Portuguese wetland area designated as SPA under the Birds Directive. Our survey indicates that local perceptions are not particularly favourable to Natura 2000, which may consequently bring additional difficulties to an implementation process that has been problematic and conceptually complex from the start, not only in Portugal, but throughout the EU. In particular, the image of Natura 2000 has been further aggravated by the perception that Natura 2000 designation represents a ban on development and thus a constraint to the economic sustainability of municipalities.